RELATIONSHIP BETWEEN RHEUMATOID ARTHRITIS DISEASE ACTIVITY AND MYELOPEROXIDASE AND CATALASE ACTIVITIES AND THIOL LEVELS - Camli, AHMET ADİL; ÇAMLI, AHMET ADİL; TAŞPINAR, ÖZGÜR; Aydin, TEOMAN; AYDIN, TEOMAN; KEPEKÇİ, MÜGE; Ozer, O. F.; ÖZER, ÖMER FARUK; Keskin, YAŞAR; Selek, S.; SELEK, ŞAHABETTİN; Mutluer, A. S. (My University, 2016)
The aim of this study is to evaluate myeloperoxidase activity, catalase activity and thiol levels at early with rheumatoid arthritis patients. Blood taken from the patients was diagnosed with RA according to American Rheumatism Association ACR 2010 criteria, but not employed the medication of DMARD (Disease-modifying antirheumatic drugs) in order to examine the antioxidant parameters of myeloperoxidase activity, catalase activity and thiol levels. Twenty nine patients with early RA and 61 healthy controls were included in the study. Peripheral blood samples were used for all the assays. The average age of the patients was 39.91 +/- 13.32 and their average BMI was 28.56 +/- 4.15. Erytrocyte sedimentation rate (ESR) and C-reactive protein (CRP) values have been found significantly high levels in RA group when we compare with control group. Catalase activity and thiol levels which means antioxidant parameters, have been found significantly low levels according to control group. When the parameters of myeloperoxidase activity were compared to the control group, the values of control group were significantly high. Stronger response in patients with early RA suggests that antioxidant markers may be useful in evaluating the progression of RA as well as in elucidating the mechanisms of disease pathogenesis.